The Impact of Training Sessions in the Development of Social Behavior to Reduce the Phenomenon of Delinquency among Young People - Fadel Kurdi Shalakha (Journal of Global Pharma Technology, 2018)
The research comes in an attempt to reveal the effect of counseling sessions on the methods of parental treatment and its role in the development of social behavior and to reduce the deviation of a sample of young people belonging to the centers and forums of youth and sports. And that the adolescent lives in a sensitive stage of his life needs to be understood and take his hand in order to be a positive and social community and integration with others and be able to take realistic goals consistent with their tendencies and potential because the social behavior The role of the sessions and the extension programs contribute to the development of social behavior and thus contribute to building a better society free of deviation and crime among young people. The study sought to identify the effect of instructional sessions on parental treatment methods in developing social behavior and reducing the phenomenon of deviation among young people. The researchers hypothesized that there are differences of statistical significance for the experimental group in the development of social behavior and reduction of Majeure deviation among young people, researchers have identified the research community, members of youth and sports forums in Najaf and researchers chose the youth forum (Ansar) as a control and the number (25) and Youth Forum (Black Rivers) as a pilot group and their number (25). After the application of the main they experiment were analyzed and the results are processed using (SPSS), has reached researchers to results, including the need for the use of extension programs and to increase awareness and use of appropriate methods of parental treatment of parents of good treatment and urged their children to integrate with others, have recommended the researchers emphasize the use of methods Democracy and desirable in dealing with their children and the impact of those methods in the development of the personality of children and the need to conduct surveys to detect the spread of positive social behavior because of its impact in reducing the phenomenon of deviation and reduce crime.Keywords: Training sessions, social behavior, phenomenon and delinquency.